2003
DOI: 10.1002/bin.139
|View full text |Cite
|
Sign up to set email alerts
|

Teaching a simple meal preparation skill to adults with moderate and severe mental retardation using video modeling

Abstract: We evaluated whether adults with mental retardation in the moderate or severe range would acquire simple meal preparation skills via video modeling. Training was conducted in the kitchen of the participants' day treatment setting. The intervention consisted of (i) watching a video of an adult with a developmental disability making a peanut butter and jelly sandwich and (ii) receiving verbal praise for each step of the task that was performed correctly. All three participants mastered the task and demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…Similarly, Lasater and Brady (1995) showed the generalization of self-help skills such as making lunch and doing laundry in two individuals with developmental disabilities and behavioral disorders. Finally, Rehfeldt et al (2003) showed the generalization across settings of sandwich-making skills in adults with moderate or severe mental retardation. Skills established by video modeling also appear to be well maintained at follow-up (Charlop & Milstein, 1989;Lasater & Brady, 1995;Rehfeldt et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, Lasater and Brady (1995) showed the generalization of self-help skills such as making lunch and doing laundry in two individuals with developmental disabilities and behavioral disorders. Finally, Rehfeldt et al (2003) showed the generalization across settings of sandwich-making skills in adults with moderate or severe mental retardation. Skills established by video modeling also appear to be well maintained at follow-up (Charlop & Milstein, 1989;Lasater & Brady, 1995;Rehfeldt et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…Typically, an individual is asked to view the videotape at the beginning of an instructional session and to then attempt the task independently. Video modeling has proven to be an effective intervention for teaching a variety of skills to persons with developmental disabilities, including conversation skills (Charlop & Milstein, 1989;Taylor, Levin, & Jasper, 1999;Wert & Neisworth, 2003), self-help or daily living skills (Lasater & Brady, 1995;Norman, Collins, & Schuster, 2001;Shipley-Benamou, Lutzker, & Taubman, 2002), complex play sequences (D'Ateno, Mangiapanello, & Taylor, 2003), simple meal preparation skills (Rehfeldt, Dahman, Copyright # 2004 John Wiley & Sons, Ltd. Young, Cherry, & Davis, 2003), and perspective taking (Charlop-Christy & Daneshvar, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Study 2 examines the clinical efficacy of social skills interventions based solely on self-regulatory training and examines the maintenance and generalization of those skills and is an extension of Gumpel and David (2000). In Study 3, a replication of the findings of Study 1 and 2 with participants with mild and moderate mental retardation will examine the applicability of the activation model for individuals with cognitive impairments since a body of research has shown that individuals with mental retardation and developmental disabilities may not be able to passively and vicariously learn social skills (Rehfeldt, Dahman, Young, Cherry, & Davis, 2003;Werts, Caldwell, & Wolery, 1996), because social learning theory theorizes that symbolic representation is a primary component of observational learning (Bandura, 1977).…”
Section: Self-regulationmentioning
confidence: 98%
“…It has produced more rapid acquisition and greater generalization than live modeling, and a number of researchers have shown that neither prompting nor positive reinforcement are necessary for skill acquisition to occur when using VM (D'Ateno, Mangiapanello, & Taylor, 2003). VM has been used to help individuals with ASD develop general purchasing skills (e.g., Haring, Kennedy, Adams, & Pitts-Conway, 1987), daily living skills (e.g., Rehfeldt, Dahman, Young, Cherry, & Davis, 2003), and conversation skills (Sherer et al, 2001). However, VM has rarely been used to teach vocational skills.…”
mentioning
confidence: 97%